Pengaruh Corporate Governance Terhadap Manajemen Pajak(studi empiris perusahaan manufaktur yang terdaftar di bursa efek indonesia periode 2011-2014) - Novitasari, Sindi Dwi (2016)
This research investigates the influence of corporate governance influences on tax management behavior. Tax management is measured by effective tax rate. Corporate governance are measured by number of commissioner, percentage of independent commissioner, and compensation of commissioner and executives,and audit committee. Company size, profitability, are used as control variables. This research sample is manufactured company selected by using method of purposive sampling. There are 40 companies fulfilling criterions. This research used multiple regression analysis. The results of this research indicates that theprofitability affect tax management significantly. Meanwhile, the number of commissioner,proportion of independent commissioners, compensation of commissioner and executive, audit committee, andcompany size, rate does not significantly influence the company's tax management.